A New Phenolate‐Ion‐Type Two‐Photon Near Infrared Fluorophore‐Based Biosensor for High‐Performance Detection of HNO. Issue 53 (3rd September 2020) - He, Moyun; Li, Chenghui; Pang, Zhenguo; Chen, Kuan; Tan, Yanfei; Huang, Yan; Lu, Zhiyun
Abstract: Although ( E )‐4‐(2‐(4‐(dicyanomethylene)‐4 H ‐chromen‐2‐yl)vinyl)phenolate anion (DCPO − ) has recently emerged as a potential near infrared (NIR) biosensor signaling unit, the p K a value of its conjugate acid is relatively high (∼9); this will lead to relatively low concentrations of DCPO − under physiological conditions and, hence, unsatisfactory sensitivity of DCPO − ‐based bio‐probes. By difluoro‐substitution on DCPO −, we have exploited a new fluorophore of o ‐FDCPO − whose conjugate acid has a much lower p K a value of 7.42. Meanwhile, o ‐FDCPO − is NIR emissive with λ em =693 nm and has a 0.76‐fold higher fluorescence efficiency than DCPO − . The significant superiority of o ‐FDCPO − over DCPO − in sensitivity for NIR biosensor applications was confirmed by comparative studies on two HNO probes, namely o ‐FDCPO‐P and DCPO‐P, which bear signaling units of o ‐FDCPO − and DCPO −, respectively. Moreover, o ‐FDCPO‐P has been demonstrated to be a high‐performance HNO probe with high selectivity, high sensitivity (detection limit: 50 nm ), and a rapid response, together with a two‐photon NIR‐excitation imaging capability. Abstract : Acid test : A new fluorine‐substituted phenolate‐anion‐type high‐performance NIR fluorophore has been developed for biosensor applications. The enhanced acidity of its conjugation acid increases concentrations of its phenolate‐anion‐typed fluorophore under physiological conditions.